A hologram for the king ebook - Eggers, Dave (2012)
From the bestselling author of The Circle —a taut, richly layered, and elegiac novel that takes us around the world to show how one man fights to hold himself and his splintering family together in the face of the global economy’s gale-force winds. “An outstanding achievement in Eggers’s already impressive career, and an essential read.” — San Francisco Chronicle In a rising Saudi Arabian city, far from weary, recession-scarred America, a struggling businessman pursues a last-ditch attempt to stave off foreclosure, pay his daughter’s college tuition, and finally do something great. A novel that’s a powerful evocation of our contemporary moment—and a moving story of how we got here.